Risk Management and Crop Insurance Adoption among Cocoa Farmers - Olowa, Omowumi Ayodele; Olowa, Olatomide Waheed (Nepalese Journal of Agricultural Sciences, 2026)
Cocoa farming in Nigeria is increasingly threatened by production and market risks, including climate shocks, pest outbreaks, and price fluctuations. Farmers,as primary producers, often lack the resources and institutional support to effectively manage these risks, making crop insurance a potentially essential tool for protecting livelihoods. This paper examines the factors influencing cocoa farmers’ adoption of crop insurance in Ekiti State, Nigeria, focusing especially on risk preferences and perceptions of insurance schemes. A total of 200 household heads were selected through multi-stage sampling across four cocoa-producing local government areas. Data on socio-demographic traits, insurance perceptions, and risk attitudes were analyzed using descriptive statistics and a binary logistic regression model. Results show that most cocoa farmers have not adopted crop insurance. Adoption was positively affected by education, household size, and debt usage, whereas membership in cooperative societies, farming experience, land ownership, and non-farm income were negatively related to insurance uptake. Notably, risk preferences did not differ significantly between insured and uninsured farmers, indicating that socio-economic factors are stronger predictors of insurance decisions. The paper concludes with policy recommendations to strengthen Nigeria’s agricultural insurance system, including reforms to the Nigerian Agricultural Insurance Corporation (NAIC), the provision of better inputs, and the creation of farmer-friendly insurance products tailored for smallholders. By tackling both institutional and behavioral barriers, crop insurance can serve as an effective tool for improving resilience and sustainability in cocoa production.